2016
DOI: 10.5539/jel.v5n3p272
|View full text |Cite
|
Sign up to set email alerts
|

The Mediation Role of Intrinsic and Extrinsic Motivation in the Relationship between Creative Educational Environment and Metacognitive Self-Regulation

Abstract: <p>This study investigated the mediation role of intrinsic and extrinsic motivation in the relationship between creative educational environment and metacognitive self-regulation. Participants were 300 girls, selected randomly from the girl hostel in university of Tehran. Participants completed Akoal’s creative educational environment questionnaire, AMS academic motivation questionnaire and self-regulated learning strategies questionnaire MSLQ. To examine reliability of measures, Cronbach alpha coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…help others) leads to more enhanced persistence and conceptual learning than providing them with an extrinsic goal. Similar results have been obtained by researchers researching the high school and college learners (Maralani, 2016).…”
Section: Introductionsupporting
confidence: 89%
“…help others) leads to more enhanced persistence and conceptual learning than providing them with an extrinsic goal. Similar results have been obtained by researchers researching the high school and college learners (Maralani, 2016).…”
Section: Introductionsupporting
confidence: 89%
“…At this point, humorous elements in the course materials can provoke curiosity towards learning. Maralani (2016) designed a creative learning environment with humorous elements and found that this environment had a positive effect on cognitive, emotional, and motivational self-regulation. Garner (2006) states that the use of humor in lectures makes students recall concepts more easily.…”
Section: Discussionmentioning
confidence: 99%
“…Otros estudios han señalado que los estudiantes motivados intrínsecamente tienden a utilizar estrategias de procesamiento más profundo de la información (Karagüven, 2012). Maralani (2016), en un estudio en el cual se utilizaron ambos instrumentos, halló un rol mediador de la motivación intrínseca en la autorregulación metacognitiva; según este estudio, los ambientes educativos promotores de creatividad incrementarían la motivación intrínseca y, en consecuencia, el uso de estrategias de autorregulación metacognitivas por parte de los estudiantes.…”
Section: Discussionunclassified